How dental students and dentists is acting and will act after applying relaxing COVID‐19 control measures (Research, Society and Development, 2022)
Objective: This study aimed to answer how dental students and dentists is acting and will act after applying relaxing COVID‐19 control measures in a Brazilian subpopulation. Methodology: This quantitative study was carried out through a questionnaire for dental students and dentists acting at private dental offices. The participants (n=240) were divided into two experimental groups: I) Group 1: undergraduate students attending the integrated clinic (n=132), and II) Group 2: professionals trained in dentistry (n=108). Results: In question 2, there was a significant difference between the group 1 and 2, in which 97.72% of the dental students are still using the N-95 mask or alternative masks during dental care service, whereas only 48.14% of the dentists still using. In question 3, there was no significant difference between the group 1 and 2, in which 40.15% and 43.51% of the dental students and dentists, respectively, still using the face shield or safety glasses during dental care service. In question 4, there was a significant difference between the group 1 and 2, in which 68.93% of the dental students intend to continue using the N-95 mask, face-shield or safety glasses during post-pandemic dental care service, however, only 50% of the dentist have the same intention. Conclusions: the majority of dental students are still using the N-95 mask or alternative masks during dental care service, and intend to continue using the N-95 mask, face-shield or safety glasses during post-pandemic period.